THE IMPACT OF YOUTH POLICY SATISFACTION QUALITY OF LIFE: FOCUSING ON THE RURAL AREAS OF SOUTH KOREA - Lee, S. (Farabi Journal of Social Sciences, 2023)
This study aimed to investigate the relationship between the satisfaction of youth with policies and their overall quality of life. Conducted through an online survey spanning from August 25th to August 31st, 2021, the survey involved 304 participants, yielding several important findings. Among the youth in Jeollanam-do Province, welfare and cultural policies garnered the highest satisfaction, while participation rights policies received comparatively lower ratings. Concerning quality of life, a sense of value in life ranked high, contrasting with relatively lower scores for an ideal life. Economically active youth reported a higher quality of life than those not engaged in economic activities. Furthermore, married youth indicated a better quality of life compared to their unmarried counterparts. Notably, a positive correlation was established between policy satisfaction and an improved quality of life. This emphasizes the potential influence of policy contentment on overall well-being. To enhance participation rights policies, policymakers should design strategies to boost participation rates, ultimately enhancing the policy experience. Policymakers need to tailor strategies based on factors like economic activity and marital status to effectively elevate well-being. Developing policies that increase youth's satisfaction can notably augment their quality of life, emphasizing the importance of well-constructed policy frameworks. Keywords: Youth, Youth policy, Policy satisfaction, Quality of life, survey